Theological Responses to the Concepts of Democracy and Human Rights: The Case of Contemporary Indonesian Muslim Intellectuals - Masykuri Abdillah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
Almost all governments in the world, including authoritarian, claiming that their political system is democratic. However, not all governments in the Muslim world accept this system. Among the 'ulama and Muslim intellectuals themselves there are differences of opinion about the system and the concept of democracy. In general, the modernist Muslim groups accept this system, because he was judged to be compatible with Islam, while Muslim groups